Evaluating the challenges of open book management in university teaching hospitals in Nigeria - Nnaji P. Amuche; Obamen Joseph; Omonona Solomon; Christian Chigozie Okonkwo (Cogent Business & Management, 2019)
Technological advancement, globalization and competition are changing the economic and social environment rapidly. As a result of this, organizations that are unable to urgently cope and adapt to these changes are underperforming because the factors for success in the past no longer holds. The paper examines challenges posed by the practice of open book management in Nigeria and provides ways the organization could brace with them for greater performance. The instrument used for gathering data from five hundred and thirty-three (533) employees in the selected university teaching hospitals in south east Nigeria is a structured questionnaire. Factor analysis was applied to determine the most common challenges of open book management in studied institutions. The study found that prominent challenges imposed by management to open book management are corruption, greed and selfishness and lack of transparency in financial/operational information. The study concludes that certain challenges are responsible for the skeptical attitude towards open book management system from the institutions studied. Even when OBM is advocated, its effective implementation is hindered as a result of the challenges. However, the study recommends a deliberate, conscious and steady effort towards the practice of OBM. Management and employees are to show serious and ongoing commitment to OBM system, since OBM is an all-inclusive tool for full engagement of employees for greater performance.
Keywords: 650; Open book management; lack of transparency; information sharing; distrust